A High Thermal Conductivity of MgO-H2O Nanofluid Prepared by Two-Step Technique - Hadia Kadhim Judran; Adnan G. Tuaamah Al-Hasnawi; Faten N. Al Zubaidi; Wisam Abed Kattea Al-Maliki; Falah Alobaid; Bernd Epple (Applied Sciences, 2022)
In this paper, the main goal is to study the impact of nanopowder volume concentration and ultrasonication treatment time on the stability and thermophysical properties of MgO-DW nanofluid at room temperature. The co-precipitation method was utilized to prepare pure MgO nanoparticles with an average particle size of 33 nm. The prepared MgO nanopowder was characterized by using XRD, SEM, and EDX analyses. Then, MgO-DW nanofluid was obtained with different volume concentrations (i.e., 0.05, 0.1, 0.15, 0.2, and 0.25 vol.%) and different ultrasonication time periods (i.e., 45, 90, 135, and 180 min) by using a novel two-step technique. With volume concentration and ultrasonication time of 0.15 vol.% and 180 min, respectively, good stability was achieved, according to the zeta potential analysis. With increasing volume concentration and ultrasonication time period of the nanofluid samples, the thermal conductivity measurements showed significant increases. As a result, the maximum enhancement was found to be 25.08% at a concentration ratio of 0.25 vol.% and agitation time of 180 min. Dynamic viscosity measurements revealed two contrasting trends with volume concentration and ultrasonication time. The lowest value of relative viscosity was gained by 0.05 vol.% MgO-DW nanofluid. The chemical and physical interactions between MgO nanoparticles and DW molecules play an important function in determining the thermal conductivity and dynamic viscosity of MgO-DW nanofluid. These findings exhibit that MgO-DW nanofluid has the potential to be used as an advanced heat transfer fluid in cooling systems and heat exchangers.